The Wrong Tools for the Job: Teachers’ Voices on Cultural Capital Mismatch - Recknagel, Crystal; Hong, Ji; Francis, Dionne Cross; Wang, Qian; Parsons, Alexandra; Lewis, Laura (International Journal of Multicultural Education, 2022)
This case study investigates how teachers in a school with a large population of low-income students of color in the U.S. perceived students’ cultural capital and associated teachers’ roles. Twenty-seven teachers were interviewed and discussed four domains of cultural capital mismatch between students and teachers: behavioral, experiential, academic, and family norm. Teachers often characterized these misalignments as students’ deficits and undertook parenting or friendship roles. This study highlights the need to support and train pre-service and in-service teachers’ critical consciousness, so that teachers leverage students’ cultural tools to enhance instruction and to counteract deficit views of students of color.